A study of the usage of business library resources by the finance faculty from B-schools in India. Issue 2 (3rd April 2023) - Paliwal, Jaiprakash M.; Raibagkar, S. S.
Abstract: India is home to more than 6, 000 Business Schools. Finance specialization is considered to be one requiring a relatively higher academic rigor. Business libraries support the knowledge requirements of the finance faculty. This research studied the usage of business library resources by the finance faculty from B-schools across India and its impact on their academic performance. A survey was conducted through a questionnaire involving more than 400 finance faculty. Two constructs, namely, usage of business library resources and academic performance, were comprehensively defined. A weighted scale evaluation was done. The finance faculty from the B-schools is lagging way behind in academic performance on high-weighted parameters like Scopus indexed journal publications. The faculty showed a relatively low usage of the business library resources. Irrationality is seen in the emphasis placed on the usage of library resources and the importance given to areas of performance. Business library resource rated with lower importance has higher usage, and those rated with higher importance show lower usage. Similarly, performance areas that were perceived to be of relatively lower importance reflect a better performance, but those which are perceived to be of much higher importance show a very low performance. It was interesting to note the low usage despite reasonable availability of quality business and finance material in the B-schools library. Suggestions are given to increase the utilization of business library resources through provisions like a compulsory library hour every day.